IMPLEMENTASI QUALITY OF SERVICE DENGAN METODE QUEUE TREE PADA KAMPUS STMIK PRADNYA PARAMITA MALANG - Setiawan, Daniel; Setyowibowo, Sigit (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
Bandwidth management on network system is very important to regulate how much bandwidth to be received by each user. One method is to use a method of bandwidth management queue tree. Queue tree method can provide a fair and equitable bandwidth according to the user that is connected to the network system. Researchers have goals implement bandwidth management with methods queue tree along maximize quality of service on campus STMIK Pradnya Paramita Malang. Internet users on campus STMIK Pradnya can get a fair and equitable bandwidth according to its use. Based on the results of tests that have been conducted by researchers, that the network system that has been created to maximize the quality of service by using the queue tree method can be implemented on campus STMIK Pradnya Paramita Malang. And students can use the internet as appropriate.Keywords: , Queue Tree, Bandwidth Management, Network System